"Insha´Allah I´ll do my homework": adapting to Arab undergraduates at an English-speaking university in Dubai. Issue 2 (1st December 2014) - Rapanta, Chrysi
Abstract : The United Arab Emirates and Dubai in particular have in recent years attracted an increased number of Western teachers for all educational levels, especially universities. As part of the orientation for a Western teacher before entering a classroom, the main differences between Western and Middle East culture are often highlighted without an effort to explain how these differences are manifested in students' behavior in courses, or to suggest how the teacher could address them. This paper aims at helping current and future faculty in their professional practice by considering Emirati Arab cultural characteristics as well as strategies adopted by the author to cope with them. Such strategies have been successful, as her students´ evaluations and academic performance distinctions during the last two years have continuously shown.